The Ties that Do Not Bind. Group formation, polarization and conflict within networks of political elites in the medieval Roman Empire - Preiser-Kapeller, Johannes (Journal of Historical Network Research, 2020)
This chapter aims at the exploration of concepts and methods of network and complexity theory as well as New Institutional Economics (NIE) for the analysis of the emergence of conflicts within ruling elites in pre-modern polities. From the point of view of NIE, Douglass C. North, John Joseph Wallis and Barry R. Weingast have pointed out the general structural weakness of pre-modern formations of power. This assumption will be tested against a comparative analysis of the structural and qualitative properties of elite networks, also in their temporal and spatial dynamics. The modelling of the relational web among elite members will also open a micro-perspective on the evolution and resilience of networks between actors within smaller groups and clusters in situations of conflict. Furthermore, it allows for a quantification of the size of conflicts within elite networks and the analysis of their temporal dynamics.